(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the priority directions, importance and the form of linguistic and ecological research developed as a new field is defined. At the same time, on the basis of the achievements in this field in world and Uzbek linguistics, the main tasks for the ecolinguistics of the Uzbek language to be fulfilled in the future were determined.